Theoretical Prerequisites for Optimizing the Spray Pattern Angles of an Adaptive Sprayer for a Field Sprayer (London Journal of Research In Science: Natural and Formal, 2024)
Vibrations of the sprayer field boom in the transverse-vertical plane result in a decrease in the quality of the technological operation. This is especially true in relation to the operation of small-sized single-support wheelbarrow-type sprayers. One of the possible solutions to compensate for the effect of transverse vibrations of the boom on the quality of spraying is the use of adaptive sprayers with a variable root angle of the spray torch, responding to the position occupied by the sprayer in relation to the surface being treated. The purpose of the work is to optimize the current values of the frontal spray angles of the nozzles of the adaptive distribution system of a small boom sprayer. The novelty of the study lies in the fact that, unlike industrial agricultural machinery, insufficient attention is paid to the implementation of technologies using small-scale mechanization tools. A prototype of a single-support boom motor sprayer was used as the object of study. The field experiment was carried out at the experimental sites of the Oryol State Agrarian University. Registration of data on the deviation of the sprayer from the vertical axis was carried out using a specially developed mathematical processing of the decrypted experimental data was carried out by a spreadsheet processor in the Microsoft Excel environment. The study of the obtained analytical dependencies was carried out in the environment of the mathematical calculation system Mathcad 14.0. The work used the method of nomogramming functions of several variables. It has been experimentally established that during operation the maximum deviations of the sprayer from the vertical can be up to 30. At the same time, the average amplitude of the transverse operating vibrations of the boom of a single-support barrow-type boom sprayer ranges from +11 to -18. The amplitude of lateral vibrations of a single-support sprayer depends on the operators preparedness and the speed of movement of the unit. Balancing the sprayer is important, aking into account the moment of forces caused by the weight of the one- sided field boom. A formula has been derived for calculating the spray width of one sprayer, taking into account the geometric parameters of a single-support sprayer, as well as its angle of inclination in the transverse-vertical plane. An analytical relationship has been obtained that makes it possible to calculate the required limits of the root angle of the spray pattern of an adaptive sprayer, taking into account the installation distance of the sprayer, relative to the vertical plane passing through the support point of the sprayer. The values of the root spray angles were found for the deflectors of adaptive sprayers, with the amplitude of oscillations of the sprayer from -18 to +11 in the transverse-vertical plane. A nomogram has been developed to determine the optimal values of the frontal angles of the spray pattern of sprayer nozzles. An analytical technique for optimizing the current values of frontal spray angles has been proposed, taking into account the position of the distribution system and performed for the first time. The practical value of the study lies in the possibility of using a formula to determine the limits of change in root spray angles when designing and developing adaptive sprayers. The technique can be used to develop software for the control complex of a sprayer equipped with an adaptive system for distributing working fluid in changing conditions.
Keywords: small-sized sprayer; sprayer; spray angle; field boom; transverse vibrations; spray uniformity; nomogram.